Quality of life among vitiligo patients attending dermatology out-patient clinics in Johannesburg - Agaba, Elisah (My University, 2017)
Introduction: Vitiligo is a skin pigmentation disorder and has an estimated global prevalence of around one to two percent. Vitiligo can significantly affect patients’ Quality of life (QoL). It is cosmetically and psychologically devastating, and can affect anyone irrespective of race, skin type or ethnicity. There is a paucity of research evaluating the QoL amongst vitiligo patients in Africa and Sub-Saharan Africa in particular. The objectives of this study were to demonstrate how vitiligo has altered the QoL of vitiligo patients treated at the skin outpatients’ clinics in Johannesburg, South Africa. Methods: Our research was a prospective cross-sectional study of all individuals who were diagnosed with vitiligo at the three dermatology outpatients’ clinics in three academic public hospitals, and the phototherapy daycare centre in Johannesburg. All patients fulfilling the inclusion criteria were requested to take part in the study. Data was obtained from enrolled individuals using a data collection sheet and the Dermatology Life Quality index questionnaire. This information was analysed using statistical software (STATA version 12). Results: A total of ninety-five (n=95) respondents were included as per inclusion criteria in our study. Our cohort comprised of sixty-two females (n=62, 65.26%), thirty-three males (n=33, 34. 74%). DLQI scores were in the ranges of 0 to 28 and the mean was 10.06±6.52, which indicates a moderate Quality of life (QoL) impairment in our cohort. Conclusion: Our study has shown that vitiligo moderately affects the QOL life of adult South African vitiligo patients. Therefore, treatment measures should be directed towards medical and psychological aspects of our patients for better treatment outcomes and improved QoL. This would be an argument for establishment of psychodermatology clinics at our referral hospitals.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the discipline of Dermatology Johannesburg, 2017
Keywords: Vitiligo Quality of Life Dermatology